The Impact of Social Networks on the Development of Students’ Social Competence - Sharov, Sergii; Шаров, Сергій Володимирович; Шаров, Сергей Владимирович; Vorovka, M.; Sharova, T.; Zemlianska, A. (My University, 2021)
The article analyzes the potential of virtual social networks for the development of social competence among young people. The authors discuss the results of the survey on students' use of virtual social networks for communication. To achieve the objective of the research and to determine the essence and meaning of social competence, methods of analysis, synthesis and generalization of the research were used. The observation method was used to identify the particularities of communication between young people in social networks. The questionnaire method was used to collect information about students' preferences regarding the choice of specific virtual social networks for communication. The results of the observations and questionnaires confirmed the suggestion that the amount of time young people spend communicating online and surfing the Internet is increasing. The results of the survey showed that 107 students from the first to the fourth year of studies at a teacher training university (Ukraine) often stay on virtual social networks by browsing them two to four times a day (51.4%). Nearly a third of students stay constantly on social networks. The most popular seem to be Instagram (83.1%) and Facebook (28%). With the help of social networks, students actively communicate with their classmates (80.4%), friends and family (78.5%). Further research is planned to explore ways to demonstrate how to avoid the negative effects of the Internet on students' personalities.
Keywords: Virtual social networks; Social competence; Information society; Internet